Geothermal resources of the eastern United States - Renner, J.L.; Vaught, T.L. (Gruy Federal, Inc., Arlington, VA (USA), 1979)
Known and potential geothermal resources of the eastern United States are reported. The resources considered are exclusively hydrothermal, and the study was confined to the 35 states east of the Rocky Mountains, excluding the Dakotas. Resource definition in these areas is based entirely on data found in the literature and in the files of a number of state geological offices. The general geology of the eastern United States is outlined. Six relatively homogeneous eastern geologic regions are discussed. (MHR)